Power Loss Analysis in Water Paddle Wheel Aerator Transmission System - NURSETYO WICAKSONO (NIM 13103030), EKO
Lately, the growth of technology has influence human thought and way of life. One of human creation is the water paddle wheel aerator. These invention are commonly used to increase the level of dissolved oxygen in the waters where organism need oxygen. But in the application, these invention has consumed a lot of electrical energy yet has a low overall efficiencies. These condition were not desireable, because it affecting the profit of consumer. The high consumption of electrical energy are mainly caused by the low efficiency of worm gear reducer which are used in the water paddle wheel aerator power transmission. In order to lower the energy consumption by increasing the gear reducer efficiencies. One of big step to achieve these were done by inventing other gear reducers which is helical gear reducer. To find out how far the changes, the testing must be done. The testing take place in land operation by adapting the load in impeller using braking mechanism with disc brake. The testing were done using 0,75 HP and 1 HP electrical motor and those two gear reducer by giving it load in several values. The result of testing shows that helical gear reducer gave much better efficiencies than worm gear reducer where the mean difference is about 26%. Still according to result of testing, the difference of motor efficiencies in their operating condition are a bit high about 6%.The result also shows that the use of 0,75 HP electrical motor coupled with helical gear reducer gave the highest value of overall efficiencies about 40% when operated in water paddle wheel aerator operating condition. These number seems to be highly differ from usual system which use worm gear reducers and 1 HP motor that only gave overall efficiencies about 34% in same condition.